1999
DOI: 10.1074/jbc.274.4.2327
|View full text |Cite
|
Sign up to set email alerts
|

Differential Immediate Early Gene Expression in Conditional Hepatitis B Virus pX-transforming VersusNontransforming Hepatocyte Cell Lines

Abstract: We report construction and characterization of tetracycline-controlled hepatitis B virus pX-expressing hepatocyte (AML12) cell lines. These cell lines were constructed in AML12 clonal isolates (clones 3 and 4), which express constitutively the tetracycline-controlled transactivator. Since pX is implicated in HCC, this immortalized hepatocyte model system was used to investigate the mechanism of pX in transformation. Clonal isolates of 3pX and 4pX lineages display conditional synthesis of pX mRNA and protein an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
137
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(142 citation statements)
references
References 69 publications
(64 reference statements)
4
137
1
Order By: Relevance
“…In this mouse model, HBx alone has no direct pathological e ect, but has accelerated tumor formation induced by c-myc. Likewise, HBx expression has been shown to lead to anchorage-independent growth of AML12 cell line, mouse hepatocyte cell line derived from TGF-a transgenic mouse (Tarn et al, 1999). In these cells, it is presumed that either c-myc or TGF-a collaborated with HBx to exhibit the transforming phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this mouse model, HBx alone has no direct pathological e ect, but has accelerated tumor formation induced by c-myc. Likewise, HBx expression has been shown to lead to anchorage-independent growth of AML12 cell line, mouse hepatocyte cell line derived from TGF-a transgenic mouse (Tarn et al, 1999). In these cells, it is presumed that either c-myc or TGF-a collaborated with HBx to exhibit the transforming phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous attempts have been made to examine the oncogenic potential of HBx in cell culture (Hohne et al, 1990;Oguey et al, 1996;Shirakata et al, 1989;Tarn et al, 1999). However, its transforming ability was barely measurable only when cells were immortalized by other oncogenes, such as SV40 T-antigen (Hohne et al, 1990) or TGF-a (Oguey et al, 1996;Tarn et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further con®rm the e ect of HBx on adherens junctions, we studied the distribution of cadherin in the 3pX and 4pX stable transfectants, derived from the murine hepatocytic cell line AML12, which express HBx in a tetracyclin-repressible manner (Tarn et al, 1999). The 3pX clone shows the features of a transformed di erentiated hepatocyte, with low HBx expression, whereas the 4pX clone displays a more dedi erentiated phenotype and higher expression of HBx (Tarn et al, 1999).…”
Section: Hbx Induces Adherens Junction Disruptionmentioning
confidence: 99%
“…A murine hepatocyte cell line AML12, established by Wu et al from a human transforming growth factor a (TGFa) transgenic mouse, 32 has been used as a cell model to study the tumorigenic activity of hepatitis B viral pX protein. 33 In this study, the investigators demonstrated that the pX protein was capable of transforming the immortalized hepatocytes as determined by anchorage-independent cell growth assay. In another study, Dumenco et al 34 showed that introduction of mutant TP53 conferred AML12 cell growth advantage rather than cell transformation.…”
mentioning
confidence: 99%